(3GdGYJHGQ aj GdfGSN hGdefShNs - (3eMeO Hf ehSi Hf YKeGf GHf MGRe, CHh HcQ, Rjf GdOjf, GdeYQha HGdMGRej,J (B584 (3g` s; (3TgGH GdOjf CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,J (B815 (3g` s
(3ChdgG (B:s
(3CfHCfG GdTjN GdEeGe CHh HcQ eMeO Hf YKeGf GdMeO ddg GdcHjQ GdeJYGd CeG HYO agPG cJGH CPcQ ajg eG EfJgJ Edi eYQaJg ef fGSN MOjK QShd Gddg Udi Gddg Ydjg hSde hefShNg s
(3BNQgG (B:s
(3aGYde Gddg Ndbg Cf GdeSjg dg Ohf Ndbg abO CWHY Gddg JYGdi HWGYg QShdg Udi Gddg Ydjg hSde JSdjekG eHGQckG BNQ GdLRA GdSGHY hHJeGeg Ke LejY cJGH GdEYJHGQ ai GdfGSN hGdefShN ef GdMOjK s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B226s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI aGJM (B(1111) s
Keywords: (3GdeLGejYs